Enhancing a culture of evidence: Using student engagement to identify problem areas which institutions can do something about - Strydom, JF; Mentz, M (South African Journal of Higher Education, 2016)
A critical component to furthering enhancement is the ability of institutional researchers to identify problem areas related to the student learning experience that institutions can do something about. By focusing on the nature of the educational process, student engagement surveys are currently used as indicators of the quality of undergraduate education in numerous countries. The second round of HEQC institutional reviews will have a strong teaching and learning focus, compelling institutions to provide evidence of how problem areas related to the student experience have been identified systematically, as well as how action plans and improvements are being implemented and monitored. This paper demonstrates how four related student engagement surveys can provide a comprehensive, longitudinal assessment of undergraduate teaching and learning in South Africa. Using a hypothetical data set, the paper illustrates how this data can be used as a diagnostic and monitoring tool in a 5-year cycle.